Numerical simulation of multistable flower-shaped composite laminates with axisymmetric layups - Padmapooja Jambulingam; Dan Wang; Hortense Le Ferrand (Scientific Reports)
Abstract Multistability is the phenomenon by which a material changes shape quickly between multiple stable states upon the application of an external trigger. Typically, fibre-reinforced composites assembled into laminates with [± 45°] or [0°/90°] layup exhibit bistability. These materials have commonly rectangular geometries, restricting their integration into more complex systems such as soft robotic actuators or biomimetic devices. One approach to increase the number of stable states is to locally vary the fibre orientation while tailoring the geometry of the bilayer laminate. This strategy is explored here using flower-shaped laminates as proof-of-concept. The dimensions of the flower’s petals as well as the local fibres’ orientations are varied using local and global coordinates systems. The morphing and the number of stable states are studied using the Finite Element Method (FEM) under various mechanical loading methods. The results demonstrate that multistability can be obtained by varying the geometry and the local fibre orientations. Generally, larger width-to-length ratios for the petals are also better for generating stable states. The simulated results are compared and discussed and could be used as a benchmark for exploring such systems in experiments or for designing even more complex multistable structures to meet the needs of soft robotics or other applications.